2018
DOI: 10.1377/hlthaff.2018.05134
|View full text |Cite
|
Sign up to set email alerts
|

How Is Telemedicine Being Used In Opioid And Other Substance Use Disorder Treatment?

Abstract: Only a small proportion of individuals with a substance use disorder (SUD) receive treatment. The shortage of SUD providers, particularly in rural areas, is an important driver of this treatment gap. Telemedicine could be a means of expanding access to SUD treatment. However, several key regulatory and reimbursement barriers to greater tele-SUD use exist, and both the Congress and the states are considering or have recently passed legislation to address these barriers. To inform these efforts, we describe how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
112
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 132 publications
(119 citation statements)
references
References 10 publications
3
112
1
Order By: Relevance
“…Appropriate measures may include telehealth to deliver care and medication treatment for OUD patients. 11 In addition, greater emphasis may be in order on the importance of social distancing and wearing masks and following other guidelines, as recommended by the Centers for Disease Control and Prevention (CDC).…”
Section: Discussionmentioning
confidence: 99%
“…Appropriate measures may include telehealth to deliver care and medication treatment for OUD patients. 11 In addition, greater emphasis may be in order on the importance of social distancing and wearing masks and following other guidelines, as recommended by the Centers for Disease Control and Prevention (CDC).…”
Section: Discussionmentioning
confidence: 99%
“…Awareness and motivation campaigns against excessive opioid use are carried out in written and visual media around the world. Several studies in developed countries have recently highlighted that opioid use is an important public health problem, and stated the necessity of limiting the use of opioids [22][23][24]. D.C. Buse et al assessed opioid use and dependence and found that 16.6 % of patients with chronic opioid use for migraine treatment met the dependence criteria and that these patients had more hospital admissions with more frequent recurrent complaints [25].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies and reports concur that MOUD saves lives and prevents relapses and other negative consequences [6; 7]. The challenge now remains how to get those affected into medical and behavioural treatment programs [3,6]. Traditional paths of entry require patients to initiate or self-present for treatment to a provider or clinic.…”
Section: Introductionmentioning
confidence: 99%